DISEÑO DE EXPERIENCIA TURÍSTICA SENSORIAL DIRIGIDO A NIÑOS DE EDAD ESCOLAR” - GAMARRA REYES GENESIS LILIBETH (2024)
The city of Babahoyo, located in the province of Los Ríos Ecuador, stands out for its history, culture and natural resources. Despite having various tourist resources, the lack of specific proposals to develop sensory tourist activities aimed at school-age children has been identified. Therefore, the need arises to design a program of sensory tourist experiences in the city of Babahoyo, aimed at school-age children to stimulate their senses in an educational way that satisfy their needs and promote their education with the natural environment and identity. Culture of the city of Babahoyo. With a research based on a non-experimental design and an exploratory scope with a quantitative approach, thus allowing us to understand the experiences and opinions of parents through surveys, in addition interviews were carried out with professionals in the field, the conclusion was reached; that in the tourism sector there is a lack of this type of activities designed especially for school-age children and the collaboration of specialists is recommended to identify strategic places for this type of activity.